The Effectiveness Of AZAM Tani Program Towards Poverty Reduction Among Participants Of Stingless Bees Honey Project: A Case Of Farmers’ Organization Authority In Kelantan. - Hyder Jaleel Gafoor Abdul Rasheed (2017)
The Area Farmers Organizations (AFO) under the supervision Farmers Organization Authority (FOA) plays a key role in the arca development concept.The active role of ATO to serve and meet farmers’ expectation known as external factor towards related program. As the organization closest to small farmers, it may well serve as its link through which development aid from the government can be channelled to the farmers.Therefore, the response by participants of stingless bees honey in AZAM Tani program under FOA in Kelantan are vital and being determine as an internal factor. AZAM Tani Program,initiate by the National Key Result Areas (NKRA) which is the government transformation program under 1 AZAM. 1 AZAM revealing that the government is serious in its efforts to improve the lives of low-income people with the goal of reducing poverty. AFO in response seriously to that initiative as a social business to drive for agriculture and rural development, makes this coordinating role of Farmers Movement a crucial one. Nevertheless, AFO are business entity, aka pre-cooperative approach, AFO give positive response and action to execute the AZAM Tani Program. The reason is a social obligation to the farmers through social business can be carried out. The different approach to manage this program compared 10 existing mainstream businesses makes the business stress situation among particular management staff.Therefore, is important to have the best approach leads to the effectiveness and success of the program. Further, the business stress exists to make AFO team more passionate and hard-working to help the poor in rural arcas. Moreover, this will strengthen the organization which promotes participation of rural residents in the economic and social life of the nation. Obviously,the vital role being part by AFO (external factor) and participants (internal factor) particularly, derive the success of the stingless bees honey project under AZAM Tani Program run by FOA at Pasir Mas District.